Anti‐anxiety drugs and fish behavior: Establishing the link between internal concentrations of oxazepam and behavioral effects - Huerta, Belinda; Margiotta‐Casaluci, Luigi; Rodríguez‐Mozaz, Sara; Scholze, Martin; Winter, Matthew J.; Barceló, Damià; Sumpter, John P. (Environmental Toxicology and Chemistry, 2016)
Psychoactive drugs are frequently detected in the aquatic environment. The evolutionary conservation of the molecular targets of these drugs in fish suggests that they may elicit mode of action–mediated effects in fish as they do in humans, and the key open question is at what exposure concentrations these effects might occur. In the present study, the authors investigated the uptake and tissue distribution of the benzodiazepine oxazepam in the fathead minnow (Pimephales promelas) after 28 d of waterborne exposure to 0.8 μg L−1, 4.7 μg L−1, and 30.6 μg L−1. Successively, they explored the relationship between the internal concentrations of oxazepam and the effects on fish exploratory behavior quantified by performing 2 types of behavioral tests, the novel tank diving test and the shelter‐seeking test. The highest internal concentrations of oxazepam were found in brain, followed by plasma and liver, whereas muscle presented the lowest values. Average concentrations measured in the plasma of fish from the 3 exposure groups were, respectively, 8.7 ± 5.7 μg L−1, 30.3 ± 16.1 μg L−1, and 98.8 ± 72.9 μg L−1. Significant correlations between plasma and tissue concentrations of oxazepam were found in all 3 groups. Exposure of fish to 30.6 µg L−1 in water produced plasma concentrations within or just below the human therapeutic plasma concentration (HTPC) range in many individuals. Statistically significant behavioral effects in the novel tank diving test were observed in fish exposed to 4.7 μg L−1. In this group, plasma concentrations of oxazepam were approximately one‐third of the lowest HTPC value. No significant effects were observed in fish exposed to the lowest and highest concentrations. The significance of these results is discussed in the context of the species‐specific behavior of fathead minnow and existing knowledge of oxazepam pharmacology. Environ Toxicol Chem 2016;35:2782–2790. © 2016 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals, Inc. on behalf of SETAC.
Keywords: dept.che